KLONING MANUSIA DALAM PERSPEKTIF ETIKA KEILMUAN DAN PENGATURAN HUKUMNYA DI INDONESIA - Masrudi Muchtar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
One result of the progress made by science and technology is human cloning. From the beginning of human cloning raises the pros and cons of various countries in the worlds. The proses of creation of human being through technology that si so feared would destroy human dignity. This will obvious impact on ethics and law. Although Indonesia has not been a country that has the ability concerning human cloning, but the creation of human beings through cloning need to have regulations that can be used to regulate the development and research on the human cloning.